ENSURING THE PROTECTION OF HUMAN RIGHTS IN LAW ENFORCEMENT - Pulatov, Yuri (International Journal of Membrane Science and Technology, 2023)
The article considers the issues of organizational and legal support in law enforcement of human rights, investigates the problems of legality of ensuring this activity, and also identifies the priority areas of activities to prevent violations of personal inviolability of citizens in the activities of law enforcement agencies: legal regulation of their activities; organizational activities of law enforcement agencies aimed at ensuring this individual right; work with law enforcement personnel and control over the activities of law enforcement agencies.